Diffusion of energy technology innovations in Portugal and perspectives for decarbonization - Bento, N.; Fontes, M. (MISTRAL European research consortium webinar, 2020)
It presents the results of the comparative analysis of the diffusion of energy technologies in Portugal in relation to the pioneer countries. It includes recent developments and reflection on the determinants of observed trends, to draw lessons for the decarbonization of systems with the characteristics of the national economy.